Agreement of two‐dimensional and three‐dimensional transvaginal ultrasound with magnetic resonance imaging in assessment of parametrial infiltration in cervical cancer. (1st March 2015) - Chiappa, V.; Di Legge, A.; Valentini, A. L.; Gui, B.; Miccò, M.; Ludovisi, M.; Giansiracusa, C.; Testa, A. C.; Valentin, L.
ABSTRACT Objectives To compare two‐dimensional (2D) and three‐dimensional (3D) transvaginal ultrasound with magnetic resonance imaging (MRI) as the gold standard in assessment of parametrial infiltration of cervical cancer and to determine if all parts of the cervix are equally assessable with ultrasound. Methods Patients with macroscopically evident and histologically confirmed cervical cancer were staged using International Federation of Gynecology and Obstetrics (FIGO) criteria and underwent MRI and 2D and 3D ultrasound examination before treatment. When assessing parametrial infiltration with 3D ultrasound and MRI, the cervix was (virtually) divided into three cylinders (cranial, middle and caudal) of equal size and each cylinder was then divided into six sectors in a clockwise manner following a consensus between radiologists and ultrasound examiners. The presence and the extent of parametrial invasion were recorded for each sector. Results of 2D ultrasound, 3D ultrasound and MRI were compared and reported in terms of percentage agreement and kappa value. Results A total of 29 consecutive patients were included in the study. The percentage agreement between 2D ultrasound and MRI in assessing parametrial infiltration (yes or no) was 76% (kappa, 0.459) and that between 3D ultrasound and MRI was 79% (kappa, 0.508). The results of 2D ultrasound showed the following agreement with those of MRI: 90% for the ventral parametrium (kappa, 0.720), 72% for the right lateral parametrium (kappa, 0.494), 69% for the left lateral parametrium (kappa, 0.412) and 58.5% for the dorsal parametrium (kappa, 0.017). The results of 3D ultrasound showed the following agreement with those of MRI: 62.5% for the ventral parametrium (kappa, 0.176), 81% for the right lateral parametrium (kappa, 0.595), 70% for the left lateral parametrium (kappa, 0.326) and 52% for the dorsal parametrium (kappa, 0.132). The best agreement between 3D ultrasound and MRI was for the middle cervical cylinder (76%; kappa, 0.438) and the poorest agreement was for the caudal cylinder (42%; kappa, 0.125). Conclusion The results of 2D and 3D ultrasound showed similar moderate agreement with MRI; 2D and 3D ultrasound examinations are less costly and more readily available than MRI and should be considered in the preoperative work‐up for cervical cancer. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.